Relationship between birth weight and total cholesterol concentration in adulthood: A meta‐analysis. Issue 1 (January 2017) - Chen, Lian‐Hui; Chen, Shan‐Shan; Liang, Li; Wang, Chun‐Lin; Fall, Caroline; Osmond, Clive; Veena, Sargoor R.; Bretani, Alexandra
Abstract : Background : Although a substantial number of studies have investigated the relationship between birth weight and serum cholesterol later in life, the results vary extensively. The aim of this study was to explore the relationship between birth weight and total cholesterol concentration in adulthood. Methods : We considered the results of several published observational studies that reported the association between birth weight and total cholesterol concentration in adulthood. The associations were assessed by linear regression coefficients. Summary regression coefficients with 95% confidence intervals (CI) were computed using random‐effects models. Subgroup and sensitivity analyses were also conducted to explore possible explanations for heterogeneity among the studies. Results : A total of 20 studies with 26, 122 participants were identified. After adjustment for adult body mass index, the summary regression coefficient for an increment in birth weight of 1 kg was −0.09 mmol/L (95% CI: −0.13, −0.05) for men without heterogeneity ( I 2 = 17.2%) and −0.08 mmol/L (95% CI: −0.13, −0.03) for women with low heterogeneity ( I 2 = 34.0%). Stratified and sensitivity analyses generally confirmed the robustness of the findings in men. However, subgroup analyses by age indicated that the association of birth weight with total cholesterol was statistically significant only in women aged <50 years. There was no evidence of publication bias in these studies. Conclusion : Based on our results, lower birth weight was found to be associated with higher concentrations of total cholesterol in men aged >18 years and in women aged <50 years.